Formation of O2-methylthymine in poly(dA-dT) on methylation with N-methyl-N-nitrosourea and dimethyl sulphate. Evidence that O2-methylthymine does not miscode during DNA synthesis. - Saffhill, R (1978)
The alternating co-polymer has been methylated with either N methyl-N-nitrosourea (MNU) or dimethyl sulphate (DMS) and the levels of the various methylated thymidines (O2-methylthymidine, 3-methylthymidine and O4-methylthymidine) measured. MNU produced all three compounds whereas DMS only produced 3-methylthymidine and O2-methylthymidine at detectable levels. These results have been combined with our earlier results concerning the misincorporation of dGMP with E. coli DNA polymerase using MNU-methylated poly(dA-dT). These results indicate that O2-methylthymidine does not miscode during DNA synthesis.